Desempenho de bioestimulantes e sua viabilidade econômica na cultura da soja - Faria, Tatiana Carvalho (2017)
The use of biostimulants has been widely applied in agricultural production, in soybean especially, and perform an important role in the growth and development of plants. The present study objectified to evaluate the biostimulants in soybean, about the application time and the environment, considering the agronomic aspects, productivity and economic viability. Two experiments were implanted, one in the greenhouse and other in the field. The design was completely randomized, factorial 6 x 3 with 4 repetitions. The treatments were: control, without product application; Stimulate® , 250 mL ha-1 ; Matrix G® , 200 mL ha-1 ; Vitakelp® , 250 mL ha-1 ; Agrostemin® , 30g ha-1 ; Improver® , 120 mL ha-1 . The times of application were in seed treatment, to 40 or 60 days after sowing. In the greenhouse, the control, Agrostemin® and Improver® obtained the same mean of the first legume insert and were higher to Vitakelp® . In the dry root mass, the Matriz G® was higher than Vitakelp® . In the field, in relation to first legume insert the Agrostemin® was better than the Improver® and Stimulate® , the Matriz G® surpassed the Improver® and the application via seed and 60 days after sowing were better. In relation to plant height in seed treatment, the control and the Stimulate® were better than Matriz G® and the Improver® . When applied 40 days after sowing, the Stimulate® had greater height than the Matriz G® . In this variable the best time for of the products application was 40 days after sowing. In number of branches, in the seed treatment, the control and the Stimulate® had more branches than Vitakelp® and Improver® . In the analysis of joint variance of the experiments the height of first legume insert, number of pods, grains and branches per plant, grain mass and productivity were better at greenhouse. Plant height stood out in the field. All treatments were better in the field at plant height and better at greenhouse in grain mass and productivity. It is concluded that the climate, nutritional and health conditions favorable for the crop cycle attenuate the effects of biostimulants in plants. The first legume insert, plant height, root dry mass and number of branches per plant, the biostimulants contribute positively. The application time influences the first legume insert, plant height and number of branches per plant, increasing them. Growing in a greenhouse brings better results. The use of biostimulants is not economically viable.